Health-Related Quality-of-Life and Associated Factors Among Children and Adolescents with Type 1 Diabetes Mellitus: A Cross-Sectional Study - Bekele BT; Demie TG; Worku F (Dove Medical Press, 2022)
Bisrat Tamene Bekele,1 Takele Gezahegn Demie,2 Frehiwot Worku2 1Clinical Governance and Quality Improvement Directorate, Zewditu Memorial Hospital, Addis Ababa, Ethiopia; 2School of Public Health, St. Paul's Hospital Millennium Medical College, Addis Ababa, EthiopiaCorrespondence: Bisrat Tamene Bekele, Clinical Governance and Quality Improvement Directorate, Zewditu Memorial Hospital, P.O. Box 316, Addis Ababa, Ethiopia, Tel +251912444904, Email bisru1122@gmail.comBackground: Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases during childhood and adolescence. It threatens the health and endangers life with consequences for the physical and emotional development of the child and adolescent. Our study aimed at determining the health-related quality-of-life (HRQoL) and factors affecting it in children and adolescents with T1DM.Methods: A hospital-based cross-sectional study was conducted among 379 randomly selected children and adolescents, 5- 18 years of age, with T1DM on follow-up at endocrine clinics from 25 August to 25 September 2021. PedsQLTM 4.0 generic core scales were used to collect the data. Paired sample t-test was used to compare children's and adolescents' self-reports and caregiver's reports. Bivariable and multivariable linear regression is used to explore to identify significant predictor factors of HRQoL.Results: Total mean score of HRQoL was 88.42± 10.82 as reported by the children and adolescents and 82.17± 12.65 reported by their primary caregivers. According to self-reports, age (β=− 0.197, p=0.028), mothers' educational status (β=0.242, p< 0.001), fathers' educational status (β=0.259, p< 0.001), fathers' occupation (β=0.170, p=0.038), frequency of insulin administration (β=− 0.132, p=0.007), diabetes duration (β=− 0.101, p=0.050), and frequency of monitoring of blood glucose (β=0.165, p=0.006) were statistically significant predictors of HRQoL, explaining 21.6% of the variability of total HRQoL scores of children and adolescents (R2=0.216, F(21,357)=5.968, p< 0.001).Conclusion: Children and adolescents with T1DM in Ethiopia have relatively good HRQoL. Increased age, longer diabetes duration, and insulin administrations of three times per day were associated with decreased HRQoL scores. Educated parents, having an employed father, and frequent blood glucose monitoring were associated with higher HRQoL scores.Keywords: adolescents, quality-of-life, children, type-I diabetic mellitus, PedsQL, Addis Ababa, Ethiopia